Renewing Horizons: Emotional Impact and Well-being in Older Adults at a Lifelong Learning University - Enhancing Socio-Healthcare Support through Emotional Intelligence and Resilience Strategies - Rosser Limiñana, Pablo; Soler Ortiz, Seila (Biomedical Journal of Scientific & Technical Research, 2024)
This pilot study, preceding a broader investigation into the entire older adult student body at the Permanent University for Adults in Alicante, Spain, explores the impact of lifelong learning on their emotional wellbeing. It seeks to identify key factors influencing their emotional states and overall well-being through the educational programs provided. Utilising descriptive and quantitative research methods, including the Ryff Scales of Well-being and Mood, this study offers a comprehensive analysis of the well-being profile of this demographic group. Findings emphasise the significance of future planning, seeking new experiences, and perceiving personal improvement in enhancing life satisfaction and self-efficacy among older learners. Furthermore, the research underscores the necessity for pedagogical adaptations to promote a proactive attitude, self-efficacy, and autonomy, ultimately contributing to improved quality of life and personal satisfaction for older adults engaged in lifelong learning. These insights pave the way for more effective and empathetic educational strategies, tailored to the unique needs of older learners. This study, preceding a broader investigation into the entire older adult student body at the Permanent University for Adults in Alicante, Spain, explores the impact of lifelong learning on their emotional well-being. It seeks to identify key factors influencing their emotional states and overall well-being through the educational programs provided. Utilising descriptive and quantitative research methods, including the Ryff Scales of Well-being and Mood, this study offers a comprehensive analysis of the well-being profile of this demographic group. Findings emphasise the significance of future planning, seeking new experiences, and perceiving personal improvement in enhancing life satisfaction and self-efficacy among older learners. Furthermore, the research underscores the necessity for pedagogical adaptations to promote a proactive attitude, self-efficacy, and autonomy, ultimately contributing to improved quality of life and personal satisfaction for older adults engaged in lifelong learning. These insights pave the way for more effective and empathetic educational strategies, tailored to the unique needs of older learners.
Keywords: lifelong learning; older adults; emotional well-being; pedagogical adaptations; self-efficacy